2021
DOI: 10.1029/2021ea001725
|View full text |Cite
|
Sign up to set email alerts
|

Calibration and Characterization of Satellite‐Borne Microwave Sounders With the Moon

Abstract: The quasi-optical components of microwave sounders were characterized with ap-7 pearances of the Moon. 8• The disk-integrated brightness temperature of the Moon was measured for per-9 ihelion and aphelion. 10• Two different models of the lunar radiance were put to the test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
(82 reference statements)
0
1
0
Order By: Relevance
“…In addition to the random scatter of observed brightness temperatures, which is the basis for the error bars in Figure 3, Burgdorf et al (2021) had found a positive bias of 5.5% in the disk-integrated flux density of the Moon as measured with MHS when compared to the model by Liu & Jin (2021a). Therefore, we have divided the flux densities at 89 GHz from AMSU-B by 1.055.…”
Section: Systematic Discrepancies Between Model and Observationmentioning
confidence: 98%
“…In addition to the random scatter of observed brightness temperatures, which is the basis for the error bars in Figure 3, Burgdorf et al (2021) had found a positive bias of 5.5% in the disk-integrated flux density of the Moon as measured with MHS when compared to the model by Liu & Jin (2021a). Therefore, we have divided the flux densities at 89 GHz from AMSU-B by 1.055.…”
Section: Systematic Discrepancies Between Model and Observationmentioning
confidence: 98%